RESEARCH TRENDS AND CONTENT ANALYSIS ON VIOLENCE AGAINST WOMEN IN NURSING (1991-2024) : HEMŞİRELİK ALANINDA KADINA ŞİDDETİN BİBLİYOMETRİSİ - Elkoca, Ayşe (Göbeklitepe Medical Science Journal, 2025)
The primary aim of this study is to present bibliometric data on articles related to violence against women in the field of nursing, published in journals indexed in the Web of Science (WoS) database. The data collected within the scope of the study were analyzed using bibliometric analysis techniques across various categories, including citation counts, co-authorship, countries, most frequently used keywords, and bibliometric coupling of documents and authors. Bibliometric analysis is defined as the quantitative analysis of publications produced by individuals or institutions within a specific period and region in a given field. In this study, VOSviewer software was utilized to create network maps and conduct bibliometric analyses. The analysis revealed that the most frequently used keyword is "women violence," and the most cited areas of research include studies on women, psychology, public health, environmental health, and occupational health. It was also observed that the highest number of publications occurred in 2022. The most prolific authors were identified as Campbell, Jacquelyn C., McFarlane, Judith, and Godoy Serpa da Fonseca, Rosa Maria, while the most influential countries were the United States, Brazil, and Australia. Furthermore, the works with the highest bibliographic coupling were Arkins (2016), Bacchus (2016), and Hooker (2012). The findings of this research provide a comprehensive perspective on violence against women and its trends, contributing to the knowledge base of academics in various aspects.